Higher Leptin Level among Mongolians with Metabolic Syndrome as a Predictor of Cardiovascular Risk (Central Asian Journal of Medical Sciences, 2017)
Objectives: The focus of our research was to determine and identify the cutoff level of leptin in Mongolian adults with metabolic syndrome (MS). Methods: This observed case-controlled study was performed with 259 adults (mean age 40.35±10.75; range 18-71 years old). A questionnaire and anthropological measurements were used for obtaining data. Fasting blood sugar, serum triglyceride, total cholesterol, HDL, adiponectin, leptin, and insulin were measured in fasting blood together with LDL and HOMA-IR calculations. Sensitivity and specificity were estimated for each leptin measurement, using MS as the outcome. These values were used to construct a receiver operating characteristic (ROC) curve. Results: Average leptin levels of the group with MS were 10.97±11.32 ng/ml and 23.86±11.32 ng/ml in males and females, respectively. The average leptin level of participants with MS was 17.23±1.59 ng/ml, which was significantly higher than the control group by 10.80±1.58. The MS exposed group had a much higher level of leptin than the control group (p